Prospective comparative study of video assisted thoracoscopic surgery versus conventional thoracostomy drainage in emyema thoracis in paediatric age group - Sharma, Shipra; Sonker, Santosh Kumar; Nirala, Sukh Lal (International Journal of Research in Medical Sciences, 2017)
Background: Approximately 1.2 million people per year are affected by pneumonia in the United States. In paediatric patients, thoracis empyema complicates pneumonia 36% to 57% of the time with a range of incidence between 0.4 and 6.0 cases per 1000 paediatric admissions. Many retrospective case series have suggested that children who experience failure of conventional chest tube therapy exhibit improvement after thoracotomy or video assisted thoracoscopic surgery (VATS), especially if the procedure is performed early, based on these reports, many paediatric surgeons have come to consider primary VATS a better approach for children suffering from thoracis empyema, A recent meta-analysis suggested that primary surgical intervention for paediatric thoracis empyema effusions was best which was prospective, randomized study done by Waite et al in adults. Methods: The present prospective study was conducted in a large teaching hospital that is a tertiary centre, department of surgery pediatric surgery unit, Pt. J. N. M. medical college & Dr. B.R Ambedkar hospital, Raipur (C.G.), India, in the year 2010. Using a random number method, patients were assigned either to a primary conventional thoracostomy arm or to a VATS arm. Those randomly assigned to the conventional thoracostomy arm had chest rube placement within 24 hours of empyema detection. If the chest radiograph obtained within 24 hours of the procedure showed significant clearing, then the thoracostomy tube was left in place until it drained <1 mL/per day for >24 hours. If there was incomplete resolution of the effusion on the follow-up chest radiograph [obvious locations] and the patient was not clinically improving, then the patient was evaluated for rescue VATS or open thoracotomy. A sample size of 30 was chosen to have an 80% power to detect a predicted deference of 4 days in the mean length of hospitalization. Results: In this study, 30 patients included between 0 to 18 years of age youngest patient was 1 year and the oldest was 14 years. Six patients (20%) were between 2 to 3 years of age. In this study, 20 (67%) were male and 10 (30%) patients were females. Out of all 30 patients, in this study 20 (67%) were male and 10 (30%) patients were females. [Sixteen (53.3%) patients had right sided disease and fourteen (46.6%) had left sided disease, no patient was found having bilateral disease. All the thirty patients were empyema Thoracis. Using a random number method, patients were assigned either to a primary conventional thoracostomy arm or to a VATS arm. Conclusions: In the present study we found that empyema thoracis can be successfully treated by thoracoscopic decortications if encountered in early phase of the disease process. To conclude early intervention of empyema thoracis with thoracoscopic decortications seems to be the worldwide accepted modality of choice.